2013 CACS International Automatic Control Conference (CACS) 2013
DOI: 10.1109/cacs.2013.6734112
|View full text |Cite
|
Sign up to set email alerts
|

Global path planning and navigation of an omnidirectional Mecanum mobile robot

Abstract: This paper develops techniques and methodologies for global path planning and navigation of a Mecanum-wheeled omnidirectional mobile robot (MWOMR). The proposed navigation system is composed of three modules: odometry, nonsingular terminal sliding-mode (NTSM) dynamic motion controller, and global path planner, which have been implemented using the SoPC technology. The odometry is constructed by using a numerical method and a kinematic model of the robot, in order to keep track of the current position and orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…There have been studies not only on the motion analysis and modeling of the omnidirectional vehicles but also on their motion planning. Various approaches concerning the motion planning were proposed, such as the dynamic inversion-based scheme for the real-time trajectory generation [17], the global path planning system composed of the odometry, motion controller, and global path planner [18], and the local reactive approach for avoiding the moving obstacles [19]. These studies aim to search for the time-optimal trajectory when vehicles with omnidirectional mobility need to avoid obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies not only on the motion analysis and modeling of the omnidirectional vehicles but also on their motion planning. Various approaches concerning the motion planning were proposed, such as the dynamic inversion-based scheme for the real-time trajectory generation [17], the global path planning system composed of the odometry, motion controller, and global path planner [18], and the local reactive approach for avoiding the moving obstacles [19]. These studies aim to search for the time-optimal trajectory when vehicles with omnidirectional mobility need to avoid obstacles.…”
Section: Introductionmentioning
confidence: 99%
“…The corresponding energy consumption is different when traveling through different trajectories under different control methods. Despite many studies on obstacle avoidance and optimal path planning [15,16], it must be pointed out that the optimal path is not necessarily the path with the least energy consumption for FWMRs. In general, shorter paths will result in reduced energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Path planning and map building is one of the issues in the field of robotics that attempts to find and optimize the path from the initial position to the final position while the local map is dynamically built up as the robot moves. There have been a large number of studies on navigation and building of an autonomous mobile robot by a variety of methodologies such as Genetic algorithms ( [1,7]), electric charge method ( [2]), map-based method ( [3]), neural networks model ( [4][5]), rapidly exploring random tree ([6]), particle swarm optimization ( [7]), ant colony optimization ( [8]). Tsai et al [1] developed parallel elite genetic algorithms model for global path planning, in which a near-optimal collision-free continuous route is generated in structured workspace.…”
Section: Introductionmentioning
confidence: 99%
“…Tsai et al [7] suggested a hybrid motion planning system by integrating PSO (particle swarm optimization) and RGA (real-coded genetic algorithm) algorithm. A numerical approach and a kinematic model of the robot are explored to construct odometry.…”
Section: Introductionmentioning
confidence: 99%